Aflatoxins, animal health and safety of animal source foods - Grace, Delia; Lindahl, Johanna F.; Atherstone, Christine; Kang'ethe, Erastus K. (International Livestock Research Institute, 2014)
This presentation summarises current knowledge on the impacts of aflatoxins on animal health and productivity. It discusses the implications of this on the benefits derived from livestock such as income and nutrition by poor people. We summarise current evidence on livestock exposure and indicate high risk practices and management options. We also summarise the evidence of transfer of aflatoxins from livestock and fish feed to animal source products, the associated risk to human health, and the options for management. We finish by highlighting key evidence gaps and present policy recommendations for managing aflatoxins in livestock and fish feed chains and in animal source foods.